Impact ot the “Peer Instruction Method” supported by “Clickers” on Basic Maths Learning - Escudero, Rafael Enrique (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2014)
This study was intended to promote greater interaction between students and focusing your attention on the under-lying concepts studied in the course basic math, in exchangefor the material in sequence presented in textbooks and class notes. The study was conducted during the first half of 2012 (2012-10) and the 2012 summer period (2012 20), through a process of joint research quantitatively and qualitatively. The number of students treated in 2012 (10) was 249 and 10in the summer period. Of the 249 randomly took a course of 37 students which was a pretest at the start of the course without having received treatment. In the last week, was applied a posttestwhen the student had received the Peer Instruction Meth-od. Equal treatment is made with the summer course. The samples came from normal distributions, which found using the Shapiro-Wilk and Chi square statistical. Found significant differences between the averages of the posttest and pretest in both courses, for which was applied a test for paired as a study before and after samples student's t. For the Group of 37 students t = 5.87212 with p = 0.0000296539 < 0.05. The Group of 10 students t = 4.39678 with p = 0.00172844 < 0.05. The confidence level was of 95%. Surveys were conducted to measure the impact qualitatively, Likert type to all students, in which stood a high favorability (more than 80%) of the method in terms of more dynamic classes, greater motivation, good learning environment, greater participation, sufficient time to answer questions and improvement in learning.